Dinner tonight : 100 simple, healthy recipes for every night of the week - Snodgrass, Alex (William Morrow, 2023)
The author understands how important it is for healthy food to be accessible in both flavor and preparation. This book provides dinners that make eating healthy a breeze, and it features meals that work for a variety of diets, which are clearly labeled on each recipe. Many dishes are created in one skillet or on a sheet pan.